A Translation Analysis of Kahlil Gibran’s “The Broken Wings” to “Sayap-Sayap Patah” by Sapardi Djoko Damono and M. Ruslan Shiddieq - Tira Nur Fitria (Badan Pengembangan dan Pembinaan Bahasa, 2024)
This research analyzes the translation between two translators in translating Kahlil Gibran’s work entitled “The Broken Wings” into ‘Sayap-Sayap Patah”. This research is descriptive qualitative. The analysis shows that the two translators have different styles of translating. The first translator, Sapardi Djoko Damono, chose a more formal and direct style in his translation, while the second translator, M. Ruslan Shiddieq, tended to use a more expressive style and prioritized artistic impressions. Sapardi Djoko Damono maintained fidelity to the original text by translating it literally, while M. Ruslan Shiddieq carried out free interpretation and created more metaphorical and creative sentences. These differences in approach result in translations that have different nuances and expressions, reflecting the translator's style and preferences. Despite their differences, both translators, Sapardi Djoko Damono and M. Ruslan Shiddieq, effectively convey the essence of Kahlil Gibran's